"A group that's just women for women": Feminist affordances of private Facebook groups for professionals. (June 2019) - Pruchniewska, Urszula
Women across a range of industries are creating women-only private Facebook groups for professional support, networking opportunities, and career development. Through interviews with 26 women, this research shows how private Facebook groups provide affordances for creating spaces reminiscent of second-wave consciousness-raising groups. Within these groups, separate from cisgender men, women discuss their work experiences and share advice, leading to changes for women beyond the groups' borders. Thus, private Facebook groups for professional women support feminist practices despite not being labeled as explicitly feminist. However, these activities are limited in their usefulness for the wider feminist project by the exclusion of some women across lines of difference such as race, class, and age. This study illustrates empirically how social media is used for everyday politics, contributing to understandings of the digital fourth wave of the women's movement.